Dokter Soeharso: Pejuang dan Pelopor Rehabilitasi Penyandang Disabilitas - Ratih Lutfita Ningtyas; Wulan Nurjanah (Jurnal Artefak, 2025)
This study examines the role of Dr. Soeharso as both a medical fighter and a pioneer of disability rehabilitation in post-independence Indonesia. Triggered by the growing number of war casualties who underwent amputations and lost limbs, this research aims to explain how Dr. Soeharso designed and implemented rehabilitation programs to restore physical function, independence, and social integration among persons with disabilities. Employing historical methods that include topic formulation, heuristic processes, source criticism, interpretation, and historiography, the study draws on archival sources from the Rehabilitasi Centrum (RC) Surakarta, Soeharso’s writings and travel reports, as well as contemporary secondary sources. The findings reveal that Dr. Soeharso developed a comprehensive rehabilitation model encompassing medical treatment, social empowerment, and economic training, which later became a foundational framework for disability rehabilitation in Indonesia. The study highlights that his efforts not only advanced equal rights and opportunities for persons with disabilities but also enriched Indonesian medical historiography and scholarship on marginalized groups.